Manjari - The Curse of her Widowhood, the Pangs of her Bodily Hungers, and the Pain of her Living all Alone in Shashi Deshpande’s ’Moving On’ - Singh, Ravindra Kumar (Integrated Journal for Research in Arts and Humanities, 2023)
Moving on highlights the alienation and loneliness of a young widow, the curse of her widowhood, the pangs of her bodily hunger and the pain of her living all by herself. Manjari, the novel's protagonist, faces new dilemmas that Sarita, Indu, Jaya, Urmi, Sumitra, and Madhu have never experienced.